PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI SMK ISLAM MBAH BOLONG WATUGALUH DIWEK JOMBANG - Dwi Khoironir Ramatulloh; Ali Said (Kampus Akademik Publiser, 2024)
Education is a means to improve and develop the quality of human resources which makes them important for life. A teacher must be able to innovate. One innovation is to find and apply learning methods that attract students' interest and allow them to participate in active learning. By making students more active in learning, of course, learning methods or media are needed that can stimulate students' learning motivation. Technological developments nowadays are very rapid and technology itself can be applied in the realm of education, such as audio-visual multimedia-based learning media called power point.Based on the problems above, this researcher has 2 objectives related to the research focus on the use of Power Point learning media in increasing student learning motivation at Mbah Bolong Islamic Vocational School, Jombang. The objectives are 1) To describe how motivated students are to learn at Islamic Vocational School Mbah Bolong Watugaluh Diwek Jombang. 2) To describe how the use of power point learning media is to increase students' learning motivation in Fiqh subjects at Mbah Bolong Islamic Vocational School and what the supporting and inhibiting factors are.The type of research used is case study research. The research was carried out using a qualitative approach with descriptive methods. Data collection was carried out using interviews, observation techniques and documentation. The informants in this research consisted of school principals, teachers and students. Data collected from observations and interviews were analyzed using data source triangulation analysis techniques From the results of the research it can be concluded that 1) The learning motivation of students at Mbah Bolong Islamic Vocational School Watugaluh Diwek Jombang has proven to be effective in the classroom. Children are more active in asking the teacher what they do not understand, and students also pay close attention to the material presented by the teacher. And students are also more enthusiastic in completing assignments given by the teacher, this is proven by satisfactory student learning outcomes. 2) Presentations that use animation, moving images and videos not only make learning more interesting, but also students are more involved and enthusiastic in understanding every detail. However, its use in the classroom is currently still limited because teacher creativity has not yet reached the top level, such as the use of animation and AI.